THE USING OF REGISTERS IN TECHNOLOGY OF INFORMATION CONTEXT APPLIED BY COMPUTER COMMUNITY - Bayu Chandra Prasetyo; Sisca Wulansari Saputri (FKIP, Universitas Banten Jaya, 2020)
This research is an ethnography study which explores the using of registers in technology of information context applied by computer community. The research examines the textual patterning of the registers applied by computer community, interpersonal and intrapersonal features as well as considers possible contextual factors which contribute to the formation of cultural theme. The research thus aims to provide both textual and contextual of the register under investigation in language and culture. For its framework for analysis, the research draws on domain analysis, taxonomic analysis, componential analysis, and the role of both textual and contextual pattern in forming cultural theme. The research reveals that computer community uses a proverb ‘Practice Makes Perfect’ as their cultural theme to understand the functional interpretation of each register in technology of information context. They seem to distance themselves from outside sources such as bilingual dictionary for comprehending the textual meaning and computer dictionary for comprehending the contextual meaning. They integrate and manipulate outside sources in various ways to establish and provide supportive for the views they express. The research concludes that cultural theme of computer community is a proverb ‘Practice Makes Perfect’. They believe that they can possess the skills by keeping practice. It is thus recommended that further study in this field should be able to investigate the need analysis of English for specific purpose in order to improve the comprehension of the register.